Generation of high-frequency topographic Rossby waves in the Gulf of Mexico - Johnson Exley, Alexis; Donohue, Kathleen A.; Watts, D. Randolph; Tracey, Karen L.; Kennelly, Maureen A. (Frontiers in Marine Science, 2022)
The Loop Current Eddy (LCE) separation cycle energizes deep circulation in the eastern Gulf of Mexico, transferring energy from the surface intensified Loop Current (LC) to the typically quiescent lower layers. To document the generation and radiation of deep energy during this cycle, an array of 24 current and pressure recording inverted echo sounders (CPIES) is deployed in the region 89°W to 86°W, 25°N to 27.5°N with the intent to capture circulation near bathymetric features thought to be important for current-topographic interactions: Campeche Bank, Mississippi Fan, and West Florida Shelf. During the nearly two-year deployment, June 2019 to May 2021, three LCE separation events are observed, during which energy injected into the deep Gulf organizes into two distinct frequency bands (1/100 – 1/20 days–1 and 1/20 – 1/10 days–1). High-frequency variability dominates the array’s northwest corner in the vicinity of the Mississippi Fan. Wave properties are consistent with topographic Rossby Waves (TRWs) with wavelengths of 150 – 300 km. Their generation coincides with each LCE separation and is attributed to an upper-lower layer resonant coupling between surface meanders and the sloping topography of the Mississippi Fan. TRWs captured by the CPIES array will likely intensify as wavelengths shorten in steeper topography along propagation pathways towards the Sigsbee Escarpment, generating hazardous currents with the potential to disrupt oil and gas operations in the region.